(untitled) (Research, Society and Development, 2021)
Human milk has nutritional and immunological components that can be degraded by slow pasteurization (62.5°C/30 minutes), which is the thermal treatment traditionally used in Human Milk Banks to ensure its microbiological safety. Therefore, it is necessary to search for technologies that promote less impact on the functional properties of this important food. Therefore, the objective of this work was to evaluate the possibility of applying emerging technologies, which are already used in the food industry, for the processing of human milk, ensuring its microbiological safety and minimizing changes in its composition. To this end, a free bibliographic search was carried out in scientific databases such as Scientific Eletronic Library Online - SCIELO, Google Academic and National Library of Medicine - Pubmed. The emerging processing technologies selected for this review were ohmic heating, high hydrostatic pressure and ultrasound, due to the potential of these techniques in terms of the inactivation of pathogenic microorganisms. Although there are few studies on the application of these technologies in the processing of human milk, it can be said that there is a high potential for the application of these technologies in the processing of this food.